Possibilities of Correction for Iron Deficiency and Intestinal Microbiocenosis Disorders in Children - L.V. Kvashnina; V.P. Rodionov; I.M. Matviienko (Zaslavsky O.Yu., 2016)
Iron deficiencies and intestinal microbiocenosis disorders in children are the most urgent problems in pediatrics. The article presents the data of our own researches on the effectiveness of the correction for iron deficiency anemia in children with intestinal microbiocenosis disorders during the combination use of iron supplements and spore-forming probiotic Lactovit Forte.